Comparative effectiveness of prostate cancer treatments for patient-centered outcomes: A systematic review and meta-analysis (PRISMA Compliant). Issue 18 (May 2017) - Jayadevappa, Ravishankar; Chhatre, Sumedha; Wong, Yu-Ning; Wittink, Marsha N.; Cook, Ratna; Morales, Knashawn H.; Vapiwala, Neha; Newman, Diane K.; Guzzo, Thomas; Wein, Alan J.; Malkowicz, Stanley B.; Lee, David I.; et al.
Abstract: Background: In the context of prostate cancer (PCa) characterized by the multiple alternative treatment strategies, comparative effectiveness analysis is essential for informed decision-making. We analyzed the comparative effectiveness of PCa treatments through systematic review and meta-analysis with a focus on outcomes that matter most to newly diagnosed localized PCa patients. Methods: We performed a systematic review of literature published in English from 1995 to October 2016. A search strategy was employed using terms "prostate cancer, " "localized, " "outcomes, " "mortality, " "health related quality of life, " and "complications" to identify relevant randomized controlled trials (RCTs), prospective, and retrospective studies. For observational studies, only those adjusting for selection bias using propensity-score or instrumental-variables approaches were included. Multivariable adjusted hazard ratio was used to assess all-cause and disease-specific mortality. Funnel plots were used to assess the level of bias. Results: Our search strategy yielded 58 articles, of which 29 were RCTs, 6 were prospective studies, and 23 were retrospective studies. The studies provided moderate data for the patient-centered outcome of mortality. Radical prostatectomy demonstrated mortality benefit compared to watchful waiting (all-cause HR = 0.63 CI = 0.45, 0.87; disease-specific HR = 0.48 CI = 0.40, 0.58), and radiation therapy (all-cause HR = 0.65 CI = 0.57, 0.74; disease-specific HR = 0.51 CI = 0.40, 0.65). However, we had minimal comparative information about tradeoffs between and within treatment for other patient-centered outcomes in the short and long-term. Conclusion: Lack of patient-centered outcomes in comparative effectiveness research in localized PCa is a major hurdle to informed and shared decision-making. More rigorous studies that can integrate patient-centered and intermediate outcomes in addition to mortality are needed. Abstract : Supplemental Digital Content is available in the text